Potential Improvements in Crop Production in Egypt and Implications for Future Water and Land Demand - Saher Ayyad; Poolad Karimi; Lars Ribbe; Mathias Becker (International Journal of Plant Production, 2024)
Similar to numerous water- and data-scarce regions, Egypt confronts a critical challenge in sustaining food production for its rapidly growing population. Consequently, the country’s water and land resources are under considerable stress and require careful management. About half of Egypt’s both annually harvested areas and renewable freshwater are allocated for cultivating rice, maize, wheat, and berseem clover. However, the extent to which crop production might be improved and how this would impact future water and land requirements remains poorly understood. We analyzed potential improvements in the production of these crops and quantified their future water and land requirements under different scenarios. Potential improvements were detected through percentile analysis in three remote sensing-derived performance indicators for each crop in the Nile Delta’s Zankalon region: (i) crop yield, (ii) crop water productivity, and (iii) transpiration fraction (transpiration to actual evapotranspiration, T/AET). We applied detected improvementsto construct plausible scenarios for Egypt’s water and land requirements to sustain domestic crop production until 2050. Our findings indicate limited potential to improve T/AET (< 4%). However, improvements of up to 27% for crop yields and up to 14% for water productivity are possible. To meet the production targets by 2050, national production must increase by 128, 78, 69, and 71% above the 2016–2020’s average for rice, maize, wheat, and berseem, respectively. Depending on the improvement levels in the developed scenarios, a total harvested land area between 5.3 and 6.4 million ha will be required by 2050, with 18% allocated to rice, 28% to maize, 36% to wheat, and 18% to berseem. Associated freshwater requirements will amount to 59–68 billion cubic meters, divided into 23% for rice, 34% for maize, 28% for wheat, and 15% for berseem. Interventions increasing yields and water productivity will benefit more the summer (rice and maize) than the winter crops (wheat and berseem). We discuss likely interventions for meeting these requirements and for sustaining the supply of these crops in Egypt.